Optimizing the photodynamic therapeutic effect of BODIPY-based photosensitizers against cancer and bacterial cells - Masood, M.A. (Elsevier Ltd, 2022)
The initiation and propagation of cancer is closely associated with bacterial infection, which generally requires the simultaneous usage of anticancer drugs and antibiotics. However, the adverse effects have increased too much due to the multiple use of chemodrugs. To tackle this problem, a successful attempt has been made by developing two BODIPY-based cationic photosensitizers, 1BDPC-Py and 1BDPC-TPP, for treating both cancer and bacterial infection. Optimization of the basic design of these photosensitizers resulted in the red-light absorption, improved 1O2 generation yield, outstanding therapeutic effects and optical physical properties for excellent imaging. The decorated cationic groups grant some highly favorable features, such as a mediated hydrophilic-lipophilic balance for improving cell penetrability, specific mitochondrial anchoring for enhanced PDT and the increased attraction towards bacterial cells for efficient photoinactivation. As a result, these photosensitizers exhibited extremely high phototoxicity and phototoxic index (PI) against breast cancer cells along with promising photodynamic activity against two bacterial species and their corresponding antibiotic resistant strains. For example, 1BDPC-Py and 1BDPC-TPP have the values of 7.8 nM and 30 nM for IC50 along with 1539 and 720 for PI against the MCF-7 cells, respectively. Similarly, both 1BDPC-Py and 1BDPC-TPP decreased the viability of S. aureus and E. coli to almost 0 at 100 nM and 400 nM, respectively. Thus, to the best of our knowledge, both of these are the first excitable BODIPY-based photosensitizers in the therapeutic window for the precise treatment of both cancer and bacterial infection. Â© 2022